Talking Faith - Qayyum, Naveen (Pakistan, 2006)
Verzio FF submission Talking FaithTalking Faith opens a window into the lives of Sarah and Azam. Two friends living the post 9/11 realities where Islam gets associated with militarism and Christian minorities face a backlash by the extremists. Their faiths are different, one is Muslim and the other Christian, but what they share is huge! Music, friendship and a human bond of commonalities. They exist under the shadow of divisions but live the hope of interfaith harmony and give dialogue a human face shared by all religions.